2001
DOI: 10.2169/internalmedicine.40.1085
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets and Endothelial Cell Interaction with Neutrophils under Flow Conditions.

Abstract: Objective The mechanism of neutrophil adhesion to the endothelium during the earliest stages of acute inflammation, especially before the induction of adhesion molecules on endothelial cells, remains unknown.Westudied the possible involvement of platelets in this process.MethodsNeutrophils were added to humanumbilical vein-derived endothelial cells (HUVEC)with or without adherent platelets in the presence or absence of adhesionblocking monoclonal antibodies (mAbs). Adhesion of neutrophils to HUVEC at dynamic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Expression of platelet surface α-granule P-selectin also is necessary for platelets to interact with neutrophils, monocytes, T cells and endothelium [2123]. Neutrophils stimulated with LPS, on the other hand, shed microvesicles having potent platelet activating activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of platelet surface α-granule P-selectin also is necessary for platelets to interact with neutrophils, monocytes, T cells and endothelium [2123]. Neutrophils stimulated with LPS, on the other hand, shed microvesicles having potent platelet activating activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism involved in leukopenia includes the ability of platelets to interact with leukocytes and induce their so-called ˝secondary capture˝. The subsequent neutrophil-endothelial interaction could contribute to the initial decrease in leukocyte number and also trigger vascular inflammation [90,91].…”
Section: Leucopenia and Thrombocytopeniamentioning
confidence: 99%
“…Recently, we demonstrated that FSS exposure was selective for Mac1 cleavage and occurred parallel to reduced binding of neutrophils to platelets and fibrinogen in suspension [8]. Fibrinogen is a Mac1 ligand that stabilizes neutrophil-platelet interactions [11]. Thus, FSS-induced ctsB release and Mac1 cleavage may serve to reduce or prevent neutrophil aggregate formation [8,12].…”
Section: Introductionmentioning
confidence: 98%